Pengaturan Jaksa Penuntut Umum Dalam Penanganan Tindak Pidana Korupsi Berdasarkan Asas Dominus Litis - Naomi Artadinata; Sahuri Lasmadi (Fakultas Hukum, Universitas Jambi, 2023)
This study aims 1) to find out the role of the Public Prosecutor in handling criminal acts in the justice system in Indonesia 2) To find out the consequences of the existence of legal ambiguity regarding the authority of the Public Prosecutor to handle criminal acts based on the principle of dominus litis. Whereas the authority investigate and prosecute in the Indonesian criminal justice system related to the dominus litis KUHAP principle is only limited to prosecution. Because the prosecutor's office only present at the preliminary examination, the investigative actions of the public prosecutor can be reflected and become the responsibility of the public prosecutor. The research method used is a type of normative legal research. The research approach used is the Statutory Approach and the Conceptual Approach. The results of the study show that the principle of dominus litis is functionalized in the arrangement the authority to stop prosecution that belongs the prosecutor's office, as stipulated in Article 140 paragraph (2) of the Criminal Procedure Code. The article regulates three components of the reasons that form the basis for stopping the prosecution, namely there isn’t enough evidence, the incident is not a crime, the case is closed by law. Abstrak Penelitian ini bertujuan untuk mengetahui dan menganalisis peran Jaksa Penuntut Umum dalam menangani tindak pidana dalam sistem peradilan di Indonesia serta akibat dari adanya kekaburan hukum tentang kewenangan Jaksa Penuntut Umum menangani tindak pidana berdasarkan asas dominus litis. Bahwa kewenangan penyidikan dan penuntutan dalam sistem peradilan pidana Indonesia terkait dengan asas dominus litis KUHAP hanya terbatas pada penuntutan. Karena kejaksaan hanya hadir dalam pemeriksaan pendahuluan, maka tindakan penyidikan penuntut umum dapat tercermin dan menjadi tanggungjawab penuntut umum. Metode penelitian yang digunakan adalah tipe penelitian hukum normatif. Pendekatan Penelitian yang digunakan adalah Pendekatan Perundang-undangan (Statute Approach) dan Pendekatan Konseptual (Conceptual Approach). Hasil penelitian menunjukkan bahwa prinsip dominus litis terfungsionalisasi dalam pengaturan kewenangan untuk menghentikan penuntutan yang dimiliki oleh kejaksaan, sebagaimana diatur dalam Pasal 140 ayat (2) KUHAP. Pasal tersebut mengatur tiga komponen alasan yang menjadi dasar penghentian penuntutan, yaitu tidak terdapat cukup bukti, peristiwa tersebut bukan merupakan tindak pidana, perkara ditutup demi hukum.